Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to prove $ \int_0^\infty e^{-x^2} \; dx = \frac{\sqrt{\pi}}2$ other than changing into polar coordinates? It is possible to prove it using infinite series?

share|improve this question
1  
Check here: en.wikipedia.org/wiki/Gaussian_integral –  Bombyx mori Aug 29 '12 at 6:55
1  
See also $\int_{\infty}^\infty e^{-x^2}\,dx$ with complex analysis and Proving $\int_{0}^\infty e^{-x^2}\,dx = \frac{\sqrt \pi}{2}$ for a few further methods (most of them without using polar coordinates). –  t.b. Aug 29 '12 at 8:37
add comment

5 Answers 5

up vote 7 down vote accepted

Method 1. Let $I$ denote the integral. Then for $s > 0$, the substitution $t = x\sqrt{s}$ gives

$$ \int_{0}^{\infty} e^{-sx^2} \; dx = \frac{1}{\sqrt{s}} \int_{0}^{\infty} e^{-t^2} \; dt = \frac{I}{\sqrt{s}}. $$

Thus for $u = x^2$,

$$\begin{align*}I^2 &= \int_{0}^{\infty} I e^{-x^2} \; dx = \int_{0}^{\infty} \frac{I}{2\sqrt{u}}e^{-u} \; du = \int_{0}^{\infty} \frac{1}{2}e^{-u}\int_{0}^{\infty}e^{-ut^2}\;dtdu\\ &= \int_{0}^{\infty}\int_{0}^{\infty} \frac{1}{2}e^{-u}e^{-ut^2}\;dudt = \int_{0}^{\infty}\frac{1}{2(t^2+1)}\;dt = \frac{\pi}{4}, \end{align*}$$

which proves the desired result. Note that this is in fact equivalent to the proof in Wikipedia.

Method 2. We assume that we are aware of the Wallis product

$$ \prod_{n=1}^{\infty} \left(\frac{2n}{2n-1} \cdot \frac{2n}{2n+1}\right) = \frac{2}{1} \cdot \frac{2}{3} \cdot \frac{4}{3} \cdot \frac{4}{5} \cdot \frac{6}{5} \cdot \frac{6}{7} \cdot \frac{8}{7} \cdot \frac{8}{9} \cdots = \frac{\pi}{2}. $$

Now, it is not hard to find that

$$ f_n(x) = \begin{cases} \left(1 - \tfrac{x^2}{n}\right)^{n} & 0 \leq x \leq \sqrt{n} \\ 0 & \text{otherwise}. \end{cases} $$

increases to $e^{-x^2}$. (Simple application of Bernoulli's inequality will suffice.) Then by monotone convergence theorem,

$$ I := \int_{0}^{\infty} e^{-x^2} \; dx = \lim_{n\to\infty} \int_{0}^{\sqrt{n}} \left(1 - \frac{x^2}{n}\right)^{n} \; dx = \lim_{n\to\infty} \sqrt{n} \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}\theta \; d\theta, $$

where we have used the substitution $x = \sqrt{n}\,\cos\theta$. Now let

$$I_n = \int_{0}^{\frac{\pi}{2}} \sin^{2n+1}\theta \; d\theta. $$

Then for $n \geq 1$,

$$\begin{align*}I_n &= \left[\sin^{2n}\theta (-\cos\theta)\right]_{0}^{\frac{\pi}{2}} - \int_{0}^{\frac{\pi}{2}} 2n \sin^{2n-1}\theta \cos\theta (-\cos\theta) \; d\theta \\ &= \int_{0}^{\frac{\pi}{2}} 2n \sin^{2n-1}\theta (1-\sin^2 \theta) \; d\theta = 2n(I_{n-1} - I_n) \end{align*}$$

and we have $I_0 = 1$ and $I_n = \frac{2n}{2n+1} I_{n-1}$. Thus

$$ I_n = \prod_{k=1}^{n} \frac{2k}{2k+1}. $$

Therefore, by Wallis product,

$$ I^2 = \lim_{n\to\infty} n \prod_{k=1}^{n} \left( \frac{2k}{2k+1} \cdot \frac{2k}{2k+1} \right) = \lim_{n\to\infty} \frac{n}{2n+1} \prod_{k=1}^{n} \left( \frac{2k}{2k-1} \cdot \frac{2k}{2k+1} \right) = \frac{1}{2} \cdot \frac{\pi}{2} $$

and we have the desired result. (Conversely, knowing $I$, it can be used to prove the Wallis product formula.)

share|improve this answer
2  
Method I is really the polar method.. –  nbubis Aug 29 '12 at 9:15
add comment

Because $x \mapsto e^x$ is convex, $\displaystyle \left( 1- \frac{u}{n} \right)^n \leq e^{-u} \leq \left( 1+ \frac{u}{n} \right)^{-n}$, so $\displaystyle \int_0^{\sqrt{n}} \left( 1- \frac{x^2}{n} \right)^n dx \leq \int_0^{\sqrt{n}} e^{-x^2} dx \leq \int_0^{\sqrt{n}} \left( 1+ \frac{x^2}{n} \right)^{-n} dx$.

We use the change of variables $x= \sqrt{n} \sin(\theta)$: $\displaystyle \int_0^{\sqrt{n}} \left( 1- \frac{x^2}{n} \right)^n dx = \int_0^{\pi/2} \cos^{2n+1} (\theta) d\theta= \sqrt{n} W_{2n+1}$, where $W_{2n+1}$ is a Wallis integral.

If $p \geq \sqrt{n}$, $\displaystyle \int_0^{\sqrt{n}} \left(1+ \frac{x^2}{n} \right)^{-n} dx \geq \int_0^p \left(1+ \frac{x^2}{n} \right)^{-n} dx$. We use the change of variables $x=\sqrt{n} \tan (\theta)$ to find: $\displaystyle \int_0^{\arctan(p)} \sqrt{n} \cos^{2n+2} (\theta) d \theta \underset{p \to + \infty}{\longrightarrow} \sqrt{n} W_{2n+2}$.

Finally, $\displaystyle \sqrt{n} W_{2n+1} \leq \int_0^{\sqrt{n}} e^{-x^2}dx \leq \sqrt{n} W_{2n+2}$. But $\displaystyle W_n \underset{n \to + \infty}{\sim} \sqrt{\frac{\pi}{2n}}$ so $\displaystyle \int_0^{+ \infty} e^{-x^2}dx= \frac{\sqrt{\pi}}{2}$.

With this method, an asymptotic development of $W_n$ gives an asymptotic development of the integral.

share|improve this answer
add comment

$$ \int_{-\infty} ^\infty e^{-x^2} \; dx =I$$
$$ \int_{-\infty}^\infty e^{-y^2} \; dx =I$$
$$\int_{-\infty}^\infty e^{-x^2}\times e^{-y^2} \; dx =I^2$$
$$\int_{-\infty}^\infty e^{-(x^2+y^2)}\; dx =I^2$$
Polar Coordinates: $x^2+y^2=R^2,-\pi\leqslant \theta\leqslant +\pi$
$$\int_{-\pi}^{+\pi} \int_{0}^ \infty e^{-(R^2)}\; R\times dR \times d(\theta) =I^2$$
$$2\times \pi \int_{0}^ \infty e^{-(R^2)}\; R\times dR =I^2$$
$$-R^2=P\implies -2Rd(R)=d(P)\implies Rd(R)=-d(P)/2$$
$$2\times \pi \int_{-\infty}^ 0 e^{(P)}d(P)/2$$
$$\pi=I^2\Longrightarrow I=\sqrt{\pi}$$
since $e^{x^2}$ is even $\implies$ ans=${\sqrt{\pi}/2}$

share|improve this answer
2  
i was looking for other method than changing into polar coordinate. possibly using infinite series –  Santosh Linkha Aug 29 '12 at 7:04
    
still thank you for your effort!! –  Santosh Linkha Aug 29 '12 at 7:17
add comment

We use the change of variables $y=x^2$. $$ \int_0^\infty e^{-x^2} \; dx = \frac{1}{2}\int_{0}^{\infty} y^{-1/2} {\rm e}^{-y} \,dy = \frac{1}{2} \Gamma(\frac{1}{2}) \,,$$

where $\Gamma(x)$ is defined by the integral, $$\Gamma( x ) = \int_{0}^{\infty} y^{x-1} {\rm e}^{-y} \,dy \,. $$

Series Method

If you are interested in series method, then you can use Watson's lemma;

share|improve this answer
2  
I am suspecting the value of Gamma(1/2) is determined according to normal curve –  Santosh Linkha Aug 29 '12 at 7:27
1  
maybe you should add $\Gamma(1-z) \; \Gamma(z) = {\pi \over \sin{(\pi z)}} \, $. With $z=1/2$ you get $\Gamma^2(1/2)=\pi$... –  draks ... Aug 29 '12 at 7:31
2  
But this does not provide the value of the integral, unless one knows the value of $\Gamma(1/2)$--which is taking the answer for granted, only in a very thinly disguised version. –  Did Aug 29 '12 at 9:54
add comment

Consider the mapping $\eta\! : \mathbb{R}^2\to \mathbb{R}$ given by $$ \eta((x,y)) = \sqrt{x^2+y^2},\quad (x,y)\in\mathbb{R}^2. $$ (1) Show that the image-measure $\lambda_2\circ\eta^{-1}$ is the measure on $(\mathbb{R},\mathcal{B}(\mathbb{R}))$ with density $$ f(z)=2\pi z 1_{(0,\infty)}(z),\quad z\in\mathbb{R}, $$ by using Dynkin's Lemma.

(2) Show that $$ \int_{\mathbb{R}^2} e^{-x^2-y^2}\,\lambda_2(\mathrm{d}x,\mathrm{d}y)=\pi $$ by using the formula for integration under measureable transformations.

(3) Use Tonelli's theorem to conclude that $$ \int_{\mathbb{R}}e^{-x^2}\,\lambda(\mathrm{d}x)=\sqrt{\pi}, $$ and now your result follows.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.